Temporal artery biopsy versus ultrasound in diagnosis of giant cell arteritis (TABUL study) - Luqmani, R (University of Oxford, 2016)
STANDARD OPERATING PROCEDURE (SOP) for COMPLETION OF BIOPSY REPORT CRF SOP No: TABUL-S-012